Readiness for learning ability through experiences - Susanto, Ratnawati (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
Learning through experience is a process that facilitates the ability to experience in observing, thinking, feeling, doing and experimenting for the formation of a 4Cs-based student competency profile (communication, collaboration, creativity, critical thinking and problem solving) which is the basis for the needs of the 4.0 revolution era. The level of student learning readiness through experience is largely determined by the teacher's ability to implement pedagogic knowledge and pedagogical competency models. The purpose of this study was to examine the readiness of students' learning abilities through experiences that were formed through the contribution of the level of pedagogical knowledge abilities and pedagogic competence models from teachers. Quantitative research with data collection instruments using Likert scale questionnaires, data analysis techniques using smart PLS, the population is 220 teachers and 220 students of public and private elementary schools in the region which is in area II of the West Jakarta Municipal Education Sub-Department, DKI Jakarta Province. The sampling technique was done by purposive side. The results showed that: (1) there was a positive and significant contribution to the ability to implement pedagogic knowledge on the pedagogical competency model, (2) there was a positive and significant contribution to the ability to implement pedagogic knowledge on learning through experience, (3) there was a positive and significant contribution to the ability to implement the model. pedagogic competence on learning through experience, and (4) there is a dominant factor from each indicator as a construct forming variables that contribute to learning through experience.